On the microstructural and functional stability of Fe-Mn-Al-Ni at ambient and elevated temperatures. (15th March 2019) - Vollmer, M.; Kriegel, M.J.; Walnsch, A.; Klemm, V.; Leineweber, A.; Niendorf, T.
Abstract: In the present study the effect of multiple aging treatments ranging from room temperature to 150 °C on the pseudoelastic behavior of previously aged bamboo-structured as well as single crystalline specimens of a Fe-34.8Mn-13.5Al-7.4Ni (at.%) shape memory alloy was investigated. No additional room temperature aging effects occurred in the initially aged bamboo-structured tensile specimen stored for two years, whereas small changes in the pseudoelastic response in single crystalline specimens stored for 96 h at elevated temperatures were seen. It appears that an average precipitate sizes of about 13 nm is sufficient to impede undesired aging effects at least at room temperature. Graphical abstract: Unlabelled Image